2023
DOI: 10.1099/jmm.0.001660
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of hybrid uropathogenic Escherichia coli strains among E. coli isolates causing community-acquired urinary tract infection

Abstract: Introduction. The main aetiological agent of urinary tract infection (UTI) is Escherichia coli , categorized as uropathogenic E. coli (UPEC). The genome of UPEC shows a high degree of plasticity, which leads to the emergence of ‘intermediary strains’ with different traits from the parental pathotypes. Gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Some studies found that the incidence of UTIs was higher in women than in men and was positively associated with higher urine acidity, higher urine calcium levels, lower urinary pH, and longer duration of urolithiasis [20]. In this study, E.coli was the most predominant bacteria with 309 isolates followed by [21]. There are many different strains of bacteria that can cause a UTI, but the most common are Escherichia coli and Klebsiella pneumoniae.…”
Section: Discussionmentioning
confidence: 52%
“…Some studies found that the incidence of UTIs was higher in women than in men and was positively associated with higher urine acidity, higher urine calcium levels, lower urinary pH, and longer duration of urolithiasis [20]. In this study, E.coli was the most predominant bacteria with 309 isolates followed by [21]. There are many different strains of bacteria that can cause a UTI, but the most common are Escherichia coli and Klebsiella pneumoniae.…”
Section: Discussionmentioning
confidence: 52%
“…Bacterial adherence assays were performed as previously described with some modifications [49] , [50] . HeLa cells [50,000 cells/well] were infected with the treated and untreated bacteria at 37 °C for 3 h in a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…These hybrids may have the ability to cause disease at multiple sites of infection. Some studies have looked to determine the frequency by which hybrid UPEC are isolated from UTIs, with reported figures between 2% and 10.5% [ 40 , 41 , 44 ].…”
Section: Introductionmentioning
confidence: 99%